Dos modos de atenção hupd'äh no Alto Rio Negro - Silva, Rafael Moreira Serra da (2025)
The Hupd'äh of the Upper Rio Negro (São Gabriel da Cachoeira/Brazil) are great storytellers. Sometimes with a playful tone, at other times with a sense of fear and seriousness, they enjoy narrating events about the origin of the world and everyday situations, which they call pinig, a term glossed as “myth” or “story” (Ramos, 2013, p. 18). These situations emerge, on the one hand, when the Hupd’äh build their houses, clean the community, organize collective work efforts, request documents, among other activities they classify as bí — a verb in the Hup language that means “to do”, “to make,” and “to work” (Ramirez, 2006, p. 49) —; on the other hand, when they hunt, fish, gather fruits from the forest, visit relatives, and perform other tasks they call k’ët ḱ̈, a term they translate into Portuguese as “passear” (“to stroll”) (ibid, 2006, p. 100). These occasions provide excellent opportunities to hear accounts of incidents they have experienced or only heard about, involving a wide range of beings known in their language as yo’òm ĩh (male gender or neutral), yo'òm ãy (female gender), or yo´òm d´äh (plural). This expression encompasses both humans and “spirits”, which I refer to in the dissertation as alter-humans, situated in conditions of authority and leadership, with whom the Hupd’äh come into contact in the city, in the community, in the forest, and in the cosmic plane. Encounters with different types of yo´òm d´äh involve feelings of joy and sadness, care and deceit, protection and danger, life and death, demanding, as we shall see, distinct modes of attention. We will seek to understand the complexity of these interactions, simultaneously symmetrical and asymmetrical, focusing on Píj Dëh, Santa Cruz do Cabari, a Hup community located in the middle Uaupés, composed mostly of low-ranking Indigenous people who coexist daily with this multiplicity of beings, occupying positions of chiefs, owners and bosses (male and female).